Design of a digital system for community services in the village of kuala II - Badariatul Lailiah; Ari Abdilah (Jurnal Mandiri IT, 2023)
In this study, the object was taken regarding a web-based community service information system in Kuala II Village, Sui Raya District. In the process of serving the community, especially in the field of making certificates in Kuala II Village, Sui Raya District, previously it was still using a manual system. Where people have to come to the sub-district office and fill out a form and come back again to inquire about the processing and also still have to come back to pick up the results. With this manual system it causes less efficient time. So a study was conducted with the aim of creating a new system that could help and speed up the process of service to the community in Kuala II Village, Sui Raya District. In this research analysis, new information was generated, namely a web-based community service information system in Kuala II Village, Sui Raya District. With this system, it is hoped that it will expedite work and facilitate the community in the process of making services. The conclusion obtained with this new system is that the community can speed up the process of making a statement from the Jelupang Village. While the advice that must be considered is the need for human resources who can run and develop the system properly.